2020
DOI: 10.3390/rs12142344
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Mangrove Forest Loss and Nipa Palm (Nypa fruticans) Expansion in the Niger Delta, 2007–2017

Abstract: Mangrove forests in the Niger Delta are very valuable, providing ecosystem services, such as carbon storage, fish nurseries, coastal protection, and aesthetic values. However, they are under threat from urbanization, logging, oil pollution, and the proliferation of the invasive Nipa Palm (Nypa fruticans). However, there are no reliable data on the current extent of mangrove forest in the Niger Delta, its rate of loss, or the rate of colonization by the invasive Nipa Palm. Here, we estimate the area of Nipa Pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 58 publications
5
24
1
Order By: Relevance
“…These figures differ by almost a fifth, and can play a significant role in the setting of conservation targets, management policies, and sustainability goals. Moreover, our mangrove results compare favourably with three studies that mapped mangroves as one class accurately: the study of Nwobi et al [19], who found that mangroves occupied an area of 9115 km 2 in 2007 and 8017 km 2 in 2017; the study of Ayanlade and Drake [23] (9965 km 2 in 1987, 9255 km 2 in 2001, and 8430 km 2 in 2011); and the study by James et al [9] (7037 km 2 in 1987 and 6824 km 2 in 2002).…”
Section: Land Cover and Change Dynamicssupporting
confidence: 79%
See 3 more Smart Citations
“…These figures differ by almost a fifth, and can play a significant role in the setting of conservation targets, management policies, and sustainability goals. Moreover, our mangrove results compare favourably with three studies that mapped mangroves as one class accurately: the study of Nwobi et al [19], who found that mangroves occupied an area of 9115 km 2 in 2007 and 8017 km 2 in 2017; the study of Ayanlade and Drake [23] (9965 km 2 in 1987, 9255 km 2 in 2001, and 8430 km 2 in 2011); and the study by James et al [9] (7037 km 2 in 1987 and 6824 km 2 in 2002).…”
Section: Land Cover and Change Dynamicssupporting
confidence: 79%
“…Based on our knowledge of the region and on the classification systems of the ESA 20m African land cover data for 2016 and the GlobeLand 30 m data for 2010, we included a grassland class in our mapping efforts, which were found to decrease in the first period (from 9421 to 7089 km 2 ) and increase in the second (8102 km 2 in 2013). Our figures for the agricultural class are significantly lower to those in Ayanlade and Drake [23], Kuenzer et al [27], and Nwobi et al [19]. However, none of these studies included a separate class for grassland but, according to their spatial outputs, appear to have mapped this together with the agricultural class.…”
Section: Land Cover and Change Dynamicscontrasting
confidence: 78%
See 2 more Smart Citations
“…However, using time series data greatly increases the number of input features, reaching dozens or even hundreds. The classifiers, such as random forest, decision tree and support vector machine [13][14][15][16], are generally required to extract the forest extent from such a large number of features. They usually need a huge amount of training samples to calibrate the classifiers.…”
Section: Introductionmentioning
confidence: 99%